The making of a quality neighbourhood park: a path model approach - Abdul Malek, Nurhayati; Mariapan, Manohar; Mohd Shariff, Mustafa Kamal (Elsevier, 2012)
The fundamental focus of this study is to gain an increasing understanding on how people interpret their leisure and recreational outdoor activities in neighbourhood parks. This paper explores and expended the attributes or construct from past literature findings in the area of use pattern, needs and preferences study towards neighbourhood parks by using Structural Equation Modeling (SEM) Technique. The model should help to evaluate quality aspects in neighbourhood parks. This paper offers knowledge contribution to the body of literature for future research in the field of Landscape Architecture as well as Park and Recreation Management.